Pharma Emerging Market’s Scaning by Look and Feel of its Opportunities and Challenges - Kumar, Parveen; Tripathy, Swagat; Dureja, Harish (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Background: By 2020, the pharmaceutical business is expected to be more than two folds i.e. US 1.3 trillion, in the E7 nations - Brazil, India, China, Mexico, Indonesia, Russia and Turkey - book keeping around for one fifth of worldwide pharmaceutical sales. The paradigm is shifting from developed markets such as the United States and Western Europe to evolving markets such as Brazil, India, China, Mexico, Indonesia, Russia and Turkey. The reasons include growth patterns in developed markets that tend to flatten due to patent expiry, stringent expectation of regulatory authority. Also, high gross domestic product growth rate, large population, high per capita income, high median age population, growing health care needs of the large middle class aging population, emerging health care and insurance sector, etc. are fascinating growth aspects of emerging markets. Objective: The present paper explores the opportunities and challenges associated with Pharmerging markets. Conclusion: The emerging markets promises for profitability, a broad range of variability is observed in drug development, regulatory filing, handling deficiency, managing post approval changes, intellectual property right issues, phase lag, rudimentary healthcare system, lack of infrastructure and markets vulnerable to policy change with regard to marketing are observed. So, it’s obvious that, there can be no “one-strategy for all” approach for emerging markets.
Keywords: local clinical development